Writing Strategies of Less Skilled ESL Writers: A Protocol Analysis - Rajoo, Margaret (1999)
This study describes the writing strategies of less skilled ESL writers in the TESL Matriculation programme of University Putra Malaysia. This study contains elements of cognitive development research that look into the mental process of individuals involving the process of utilising language, and the personality of the writer. The study used writers' think-aloud protocols which provide valuable insights into the on-going cognitive and metacognitive processes and strategies that writers engage in while writing. In addition, writers' completed essays were also used as data base for analysis and discussion. The researcher presents the writing strategies of the four writers that were identified and appraises the results of the writing strategies of these writers using the Flower and Hayes' (1981a) Cognitive Process Model of Composing. Analysis of the data revealed that although a significant number of writing strategies identified in this study were uniformly distributed among all the four less skilled ESL writers of this study, some strategies, however, were unique to one or two writers only. The study also revealed that while some of the writing strategies of less skilled ESL writers identified support earlier findings of previous related studies, there are others that failed to concur with the findings of previous related studies.